Flexible screen-printed organic electrochemical transistors - Zhao, Huifeng (Nanyang Technological University, 2023)
Since the invention of transistors in 1947, the speed of innovation for modern technology has been rapid. While silicon-based complementary metal-oxide semiconductor (CMOS) circuits are well known for enabling high-speed processing in chips, the rigid nature of silicon wafers limits the application of CMOS technology in other fields which require flexible materials. As such, organic electronic circuits based on organic electrochemical transistors (OECTs) have gained high attention in recent years due to their printability, flexibility, and low voltage operation. Owing to its ability to function at low voltages, OECTs are suitable for the bioelectronic fabrication since most of biological reaction or species are occurred in an electrolyte medium. Despite their remarkably high transconductance, OECTs rely heavily on structure and dimensions of printed electrodes. Amongst several types of fabrication techniques, screen-printing offers a good tradeoff between cost and effectiveness. However, screen-printing is not one-size-fits-all and requires fine-tuning for different types of pastes. This FYP project aims to optimise printing parameters for the 4 types of pastes used in creating an OECT, namely silver, carbon, semiconducting organic polymer and insulator. Printing parameters such as print pressure, print speed and print-modes were varied and pastes were printed individually on separate substrates first. The printed substrates were then analysed accordingly to determine the best combination of parameter. Lastly, the chosen parameters for each paste are used to print complete devices for electrical testing.